2011
DOI: 10.1002/acr.20525
|View full text |Cite
|
Sign up to set email alerts
|

Racial and ethnic disparities in disease activity and function among persons with rheumatoid arthritis from university‐affiliated clinics

Abstract: Background Health outcomes in rheumatoid arthritis (RA) have improved significantly over the past two decades. However, research suggests that disparities exist by race/ethnicity and socioeconomic status, with certain vulnerable populations remaining understudied. Our objective was to assess disparities in disease activity and function by race/ethnicity and explore the impact of language and immigrant status at clinics serving diverse populations. Methods A cross-sectional study of 498 adults with confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 31 publications
6
77
0
2
Order By: Relevance
“…Few studies have investigated the interaction between cultural/geographical background and response to treatment in RA. Recent studies found racial/ethnic differences in PROs of function and global disease assessments [147,148]. These discrepancies could result from differences in interpretation and completion of outcome instruments, which, although often transculturally validated, may not guarantee transcultural comparability of results.…”
Section: Social Aspects Of Response To Therapymentioning
confidence: 99%
“…Few studies have investigated the interaction between cultural/geographical background and response to treatment in RA. Recent studies found racial/ethnic differences in PROs of function and global disease assessments [147,148]. These discrepancies could result from differences in interpretation and completion of outcome instruments, which, although often transculturally validated, may not guarantee transcultural comparability of results.…”
Section: Social Aspects Of Response To Therapymentioning
confidence: 99%
“…[23] обратили внимание на некоторые особенности, зависящие от этнического происхождения и социально-экономического статуса пациентов. У боль-шой группы больных РА (n=498) с использованием моде-ли мультивариабельной линейной регрессии авторы про-анализировали следующие параметры: пол, возраст, обра-зование, активность заболевания по DAS 28, качество жизни (HAQ) и др.…”
Section: странаunclassified
“…We believe that increased reporting of patient demographic information, particularly race and ethnicity, could shed light on the reasons for the disparities in outcomes seen in minority patients in clinical practice (7). This increased reporting will also improve the interpretability of results from trials of biologic agents in RA to specific patient populations and clarify the generalizability of these results for our increasingly diverse patient population.…”
Section: To the Editormentioning
confidence: 99%